Bilirubin Levels at 1st and 3rd Postoperative Months are Significant in Determining the Success of the Kasai Portoenterostomy - Ülgen Çeltik; Gözde Sakul; Miray Karakoyun; Mustafa Orkan Ergün (Galenos Yayinevi, 2021)
Aim:The aim of this retrospective study was to determine the indicators of survival with native liver (NLS) of patients operated for biliary atresia (BA).Materials and Methods:This review included 53 BA patients in a 13-year period. There were two groups: (1) NLS and (2) necessitating transplantation. Age at operation, and bilirubin levels on the 7th day, 1st and 3rd months postoperatively were recorded. Mann-Whitney U and logistic regression analysis were used for statistical analysis for NLS and liver transplantation (LTx).Results:Kasai portoenterostomy (KPE) was performed on 38 patients, and 15 were directed to LTx due to cirrhotic liver at presentation. Twentythree of 38 patients with KPE survived with native liver, and 15/38 patients required LTx during follow-up. Mean age at portoenterostomy for NLS and necessitating LTx was 54.43±24.64 and 68.33±24.35 days respectively (p>0.05). The 1st and 3rd month bilirubin levels were lower in the NLS group (p<0.01). The 1st month and 3rd month bilirubin levels after KP were significant predictors for survival with NLS. A cut-off value of 5.7 mg/dL bilirubin level at the 1st month predicted the necessity of transplantation after KPE with a sensitivity of 83.3% and specificity of 78.9%.Conclusion:Bilirubin levels of the 1st and 3rd months are reliable predictors for the success of portoenterostomy.